2015
DOI: 10.1111/bij.12546
|View full text |Cite
|
Sign up to set email alerts
|

Once a land of big wild rivers: specialism is context-dependent for riparian snails (Pulmonata: Valloniidae) in central Europe

Abstract: Specialist species may be perceived as such because of their narrow ecological requirements, but this may be context‐dependent. The genus Vallonia (Gastropoda Pulmonata: Valloniidae) includes widespread generalist species and also two specialists endemic to Central Europe: Vallonia suevica, restricted to warm, wet meadows and riverbanks subject to seasonal flooding; and Vallonia declivis, living only in wet to humid meadows, riverbanks, and reedbeds. Both have experienced dramatic declines; as is the case with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 113 publications
(124 reference statements)
0
8
0
Order By: Relevance
“…Previously in this journal, Altaba () presented an original hypothesis on the dispersal of small wetland snails in Central Europe after the Last Glacial Maximum, based on the discovery of rare species of the genus Vallonia at the foot of the Devín Hill, facing the confluence of the Morava and Danube Rivers, in Slovakia on the borders with Austria. Given the occurrence of these species in rivers further north, he suggested that the patterns of distribution could be explained by the transport of these snails by fish.…”
Section: Critical Identification Characters Of Vallonia Species and Dmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously in this journal, Altaba () presented an original hypothesis on the dispersal of small wetland snails in Central Europe after the Last Glacial Maximum, based on the discovery of rare species of the genus Vallonia at the foot of the Devín Hill, facing the confluence of the Morava and Danube Rivers, in Slovakia on the borders with Austria. Given the occurrence of these species in rivers further north, he suggested that the patterns of distribution could be explained by the transport of these snails by fish.…”
Section: Critical Identification Characters Of Vallonia Species and Dmentioning
confidence: 99%
“…Although such transport is well‐attested for the glochidia larvae of unionid bivalves, it has never been directly recorded for terrestrial snails. Nevertheless, improbable as such a dispersal mechanism might appear, the pattern of distribution shown in Altaba () is certainly not incompatible with it, and it raises many questions about the dispersal of land snails in this region.…”
Section: Critical Identification Characters Of Vallonia Species and Dmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of the program MONDAU, we surveyed a part of the local fauna. In contrast to recent faunistic floodplain studies, where most attention was paid to birds (Hatten & Paradzick ; Utschick et al, ), fish (Lasne et al, ; Pander et al, ), mollusks (Cejka & Hamerlik ; Horackova et al ; Altaba ), amphibians (Ponsero & Joly ), and aquatic invertebrates (Bunn & Arthington ), we focused on the biodiversity of beetles living terrestrially. Beetles colonize almost all ecological niches (Gomez‐Rodriguez et al ) and they are represented in Germany by ca.…”
Section: Introductionmentioning
confidence: 99%